2016
DOI: 10.1002/ccd.26555
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy pulse rate reduction during diagnostic and therapeutic imaging in the cardiac catheterization laboratory: An evaluation of radiation dose, procedure complications and outcomes

Abstract: Reducing fluoroscopy pulse rates to 7.5 from 10 is an effective way to reduce patient radiation exposure across meaningful dose indices. A pulse rate of 7.5 p/s is safe, with no difference in complications or outcomes. A fluoroscopy pulse rate of 7.5 p/s should be given strong consideration for a new standard. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, Sadamatsu et al [20] described that a change in the frame rate from 15 f/s to 7.5 f/s for fluoroscopy could significantly reduce AK (701.4 ± 427.9 mGy vs. 936.8 ± 623.9 mGy; p=0.02). Moreover, Hansen et al [21] found that when the frame rate was decreased from 10 to 7.5 f/s during the PCI procedure, AK significantly reduced (703.0 vs. 621.0; p=0.041). There was no difference between the two groups with regard to complications and MACE at 30 days and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sadamatsu et al [20] described that a change in the frame rate from 15 f/s to 7.5 f/s for fluoroscopy could significantly reduce AK (701.4 ± 427.9 mGy vs. 936.8 ± 623.9 mGy; p=0.02). Moreover, Hansen et al [21] found that when the frame rate was decreased from 10 to 7.5 f/s during the PCI procedure, AK significantly reduced (703.0 vs. 621.0; p=0.041). There was no difference between the two groups with regard to complications and MACE at 30 days and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…A study on cardiac catheterization showed reducing fluoroscopy pulse rate from 10 frame/second (f/s) to 7.5 f/s can reduce radiation dose by 21%. 59 A study on carotid artery stenting showed that a reduction of pulse rate from 7.5 to 4 f/s reduced radiation dose by about 51%, with no increase in procedure complication. 60 Operators should find out the minimal pulse rate appropriate for the specific procedure and provide training to staff.…”
Section: X-ray Positioning and Modesmentioning
confidence: 99%